Streptococcus mutans in plaque from margins of conventional and high copper amalgam restorations - (:unkn) unknown (My University, 1992)
Levels of Streptococcus mutans in plaque samples from margins of conventional and high copper amalgam restorations were compared in fourteen patients, each having one conventional amalgam filling in each quadrant and one high copper amalgam filling on the contra-lateral side were examined. The percentage of S. mutans of total CFU count in plaque was higher on conventional amalgam than on high copper amalgam. The difference was statistically significant (p < 0.01).
Keywords: Adult; Humans; Adolescent; Colony Count, Microbial; Streptococcus mutans; Copper; Dental Plaque; Dental Amalgam